2006
DOI: 10.1111/j.1365-2036.2006.00022.x
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of serum pepsinogen with histological atrophy following successful Helicobacter pylori eradication

Abstract: SUMMARYBackground Levels of pepsinogen have been reported to correlate with the degree of gastric atrophy in Helicobacter pylori-infected gastric mucosa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
4
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 29 publications
(33 reference statements)
2
4
0
Order By: Relevance
“…Furthermore, it has been suggested that PG II could be an even better marker for this difference than PG I [ 22 ] [ 23 ]. This was confirmed by a study by Kawai and colleagues who showed that similar PG I/II levels were found 2 months after eradication and that these levels were comparable 12 and 24 months after treatment [ 24 ]. In the follow-up test, the PG I/II ratio showed an increase.…”
Section: Discussionsupporting
confidence: 69%
“…Furthermore, it has been suggested that PG II could be an even better marker for this difference than PG I [ 22 ] [ 23 ]. This was confirmed by a study by Kawai and colleagues who showed that similar PG I/II levels were found 2 months after eradication and that these levels were comparable 12 and 24 months after treatment [ 24 ]. In the follow-up test, the PG I/II ratio showed an increase.…”
Section: Discussionsupporting
confidence: 69%
“…Using the percentage change in the sPG I/II ratio between pre‐eradication and post‐eradication, the authors proposed that an increase in the sPG I/II ratio is a reliable biomarker for successful H. pylori eradication. In the present study, decreased sPG I and an increased sPG I/II ratio after eradication were maintained during all follow‐up time points (≥ 36 months), with no significant differences between the H. pylori ‐eradicated and H. pylori ‐negative groups, which is consistent with the findings of previous studies …”
Section: Discussionsupporting
confidence: 93%
“…However, in European countries, the cut‐off values for sPG I and the sPG I/II ratio are ≤56 ng/mL and ≤ 5, respectively, for a fundic atrophy diagnosis . This non‐invasive serological marker has been found to be a predictor of H. pylori eradication . Osumi et al .…”
Section: Discussionmentioning
confidence: 99%
“…The PG I/II ratio is a widely accepted indicator for gastric atrophy, and an increase in this ratio is also considered as an result of the successful H. pylori eradication. 26 Another study also reported that the percentage changes in serum PG I/II ratios revealed the high relation to the outcome of eradication therapy for H. pylori. 11 Taken together, H. pylori eradication contributes to the improvement of gastric cell secretion and the reversibility of atrophic gastritis, and the reduction ratio of H. pylori IgG antibodies might be related to the improve-ment of gastric mucosal atrophy.…”
Section: Discussionmentioning
confidence: 97%